2018
DOI: 10.1016/j.ijpe.2018.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Service innovation in sustainable product service systems: Improving performance under linguistic preferences

Abstract: Sustainable product service systems enable firms that are operating under resource limitations to deliver the best possible outcomes in terms of social well-being and economic growth. However, prior studies have not yet investigated the function of service innovation in sustainable product service systems or analyzed the convergence of importance and performance weighting in maximizing resource utilization in the supply chain. Moreover, prior studies have not yet integrated and proposed a complex interrelation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 71 publications
0
39
0
1
Order By: Relevance
“…Service innovation refers to services that are different from those that consumers knew from previous occasions. In other words, the organization provides services different from consumers' previous consumption experiences [30,31]. Drejer [32] suggested that service innovation is not merely the development of new products or services, but also innovative activities that revise and improve current products, services, and delivery systems.…”
Section: Service Innovationmentioning
confidence: 99%
“…Service innovation refers to services that are different from those that consumers knew from previous occasions. In other words, the organization provides services different from consumers' previous consumption experiences [30,31]. Drejer [32] suggested that service innovation is not merely the development of new products or services, but also innovative activities that revise and improve current products, services, and delivery systems.…”
Section: Service Innovationmentioning
confidence: 99%
“…Sustainable marketing is "a management conception which attends to the environmental and social demands and eventually turns them into competitive advantages by delivering customers value and satisfaction" (Belz & Karstens, 2010, p. 3). A wide view of sustainable marketing regards it as the adoption of sustainable business practices that create better businesses, better relationships and a better world (Tseng, Wu, Chiu, Lim, & Tan, 2018).…”
Section: Sustainable Marketingmentioning
confidence: 99%
“…In order to reduce the difference of evaluation results caused by different measurement units, it is necessary to deal with the criteria of learning performance evaluation in dimensionless way. According to [24,28,[46][47][48]53], different types of criteria have different dimensionless methods which are shown below.…”
Section: Solution Methodologymentioning
confidence: 99%
“…If the evaluation values are linguistic values, the dimensionless processing of qualitative criteria requires quantitative conversion of qualitative evaluation values [53]. The basis of converting linguistic value into triangular fuzzy number is shown in Table 1, which is applied to the case study in this study.…”
Section: Solution Methodologymentioning
confidence: 99%